Exploring how video conferencing impacts students' cognitive, emotional, and behavioral engagement - Hastomo, Tommy; Kholid, Muhammad Fikri Nugraha; Muliyah, Pipit; Septiyana, Linda; Andewi, Widi (UIN Raden Mas Said Surakarta, 2024)
Video conferencing has become an essential tool in the realm of education, offering educators a plethora of features to enhance student learning. This study delved into the comparative impact of video conferencing and Learning Management Systems (LMS) on student engagement in online education. The primary objective was to discern the most effective mode of communication for fostering student engagement in online learning, examining cognitive, emotional, and behavioral dimensions of engagement. The researchers used a quasi-experimental design with a historical cohort control group to compare the effectiveness of Zoom and Moodle (LMS) on student engagement. The study involved English education students from a private university in Indonesia, with 20 students in each group. Data collection included recording online interactions, conducting semi-structured interviews, and administering a Likert-style survey. Data analysis involved content analysis, thematic analysis, and the Mann-Whitney U test. The findings underscored the advantages of utilizing Zoom, particularly in nurturing interpersonal relationships among students. Notably, the platform enhanced intimacy and interactivity within the learning environment, bolstering students' intrinsic motivation. Moreover, indicators such as creativity and idea exchange pointed towards heightened cognitive engagement facilitated by Zoom. Additionally, Zoom emerged as a practical tool for fostering social interaction and stimulating higher-order thinking during discussions. Consequently, these results provide compelling evidence supporting the integration of Zoom to enrich learning experiences and promote deeper engagement among students, both practically and theoretically.